O relacionamento fraterno na presença da deficiência - Chacon, Miguel Claudio Moriel [UNESP] (My University, 2010)
This research was developed during four years, in different regions of the country. Its purpose was to better understand the possible influences that handicapped siblings have on the development of non- handicapped siblings. Participated in the study 80 siblings, with ages ranging between 14 and 26 years. There were 20 siblings of physical handicapped (PH), 20 siblings of auditory handicapped (AH), 20 of mental handicapped (MH), and 20 of non handicapped, in number and ages equivalent.The participants answered a questionnaire containing “characteristics of handicapped person”, “characteristics of respondent sibling”, “characteristics of family”, a questionnaire with eleven closed questions and one open, but for the control group there was on less question. The phenomena studied in this research in some situations present themselves differently for each group of respondent sibling (ex: greater concern of the parents with the MH sibling, calling attention more for siblings of PH and MH, more responsibility in the family, taking care of the handicapped sibling, fear of having handicapped children, and the perception of (in) dependency of the handicapped sibling) and in others present themselves in similar manner (ex: more concern of the parents with the brother with PH, nature of the relationship, to feel or not ashamed of the sibling, talking about the sibling development). In conclusion, some phenomena, so far socially perceived as causing differences in sibling relations and attributed to de presence of a handicap are not, since between siblings of non handicapped these same phenomena present themselves in a similar way. Differently from the control group, siblings of handicapped need correct information, as well as therapeutic support to elaborate feelings of fear, anger, shame that they may have due to their condition. It is important to stress, also, the need that these siblings have to be themselves without the stigma of sibling of handicapped.

Esta pesquisa desenvolveu-se em quatro anos em diferentes regiões do país. Objetivou entender melhor as possíveis influências que irmãos deficientes têm sobre o desenvolvimento de irmãos não deficientes. Participaram 80 irmãos com idade entre 14 e 26 anos, sendo 20 irmãos de deficientes físicos (DF), 20 de deficientes auditivos (DA), 20 de deficientes mentais (DM), e 20 irmãos de não deficiente, em número e idades equivalentes. Os participantes preencheram um formulário contendo “características da pessoa deficiente”, “características do irmão respondente”, “características da família”, um questionário com onze questões fechadas e uma aberta, sendo que para o grupo-controle havia uma questão a menos. Os fenômenos estudados nesta pesquisa em algumas situações apresentaram-se diferentemente para cada modalidade de irmão respondente (ex: preocupação maior dos pais para com o irmão DM, necessidade de maior cuidado e atenção para o irmão deficiente, chamar muito a atenção para irmãos de DF e DM, maior responsabilidade na família, cuidar do irmão deficiente, medo de gerar filhos deficientes, e a percepção da (in)dependência do irmão deficiente) e em outras apresentaram-se de maneira análoga (ex: preocupação maior dos pais para com o irmão DF, natureza da relação, sentir ou não vergonha do irmão, conversar sobre o desenvolvimento do irmão). Concluindo, alguns fenômenos, até então socialmente percebidos como causadores de diferenças na relação fraterna e atribuídos à presença da deficiência não o são, pois entre irmãos de não deficientes esses mesmos fenômenos mostram-se de maneira bastante semelhante. Diferentemente do grupo-controle, os irmãos de deficientes precisam de informações corretas, bem como de apoio terapêutico para elaborar sentimentos de medo, raiva, vergonha que possam ter em função de sua condição. Cabe salientar, também, a necessidade que estes irmãos têm de serem eles mesmos sem o estigma de irmãos de deficientes.
Fraternal relationship between children with disabilities and their siblings
Keywords: Deficiência; Familia; Irmãos; Sistema Fraterno